2019
DOI: 10.1016/j.freeradbiomed.2019.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Omics analysis of oxysterols to better understand their pathophysiological role

Abstract: High amounts of cholesterol have been definitely associated with the pathogenesis of several diseases, including metabolic and neurodegenerative disorders, cardiovascular diseases, and cancer. In all these pathologies the exacerbation of pro-oxidant and inflammatory responses is a consistent feature. In this scenario, species derived from enzymatic and non-enzymatic cholesterol oxidation, namely oxysterols, are strongly suspected to play a primary role. The consideration of these bioactive lipids is therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 103 publications
(102 reference statements)
0
28
0
Order By: Relevance
“…For example, increased levels of oxysterols have been implicated in Alzheimer's disease (AD), atherosclerosis, type 2 diabetes, and cancer [7][8][9]. In addition, in mice and humans blood steroid concentration changes with age, [10][11][12] and longitudinal studies have identified a correlation between age-related decline in steroid hormones and metabolic syndrome (MetS) as well as cardiovascular disease (CVD) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, increased levels of oxysterols have been implicated in Alzheimer's disease (AD), atherosclerosis, type 2 diabetes, and cancer [7][8][9]. In addition, in mice and humans blood steroid concentration changes with age, [10][11][12] and longitudinal studies have identified a correlation between age-related decline in steroid hormones and metabolic syndrome (MetS) as well as cardiovascular disease (CVD) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Again, in Table 2, the content of 7KC and 7βOHC did not show any significant difference between treated and untreated cells. Moreover, a slight significant decrease was observed for 7αOHC, the only B ring enzymatic oxysterol of pathophysiological relevance [14,15]. With regard to the side chain oxysterol of major relevance detectable in human peripheral blood, 24OHC and 25OHC were practically undetectable in H295R cells both mitotane-treated or not.…”
Section: Effect Of Mitotane On Cholesterol Precursors and Oxysterols mentioning
confidence: 94%
“…In that in vitro study, employing the ACC reference cell line H295, relatively high concentrations of mitotane were reported to overturn cholesterol synthesis and lead cells to apoptosis, possibly through the induction of endoplasmic reticulum (ER) stress. Mitotane was demonstrated to markedly increase the steady-state level of cholesterol precursors lanosterol and lathosterol in H295 ACC cells, but also a couple of oxysterols of non-enzymatic origin, namely 7-ketocholesterol and 7β-hydroxycholesterol [13], the latter two compounds being well known as potentially toxic lipid oxidation products [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Two receptors that may be activated in obesity and could explain the increased efficacy of targeted therapy in obese patients are liver X receptor (LXR) and G protein-coupled estrogen receptor (GPER). LXRs bind oxysterols, bioactive lipids derived from cholesterol, which are elevated in obesity [101,102]. Activation of LXR and the subsequent induction of tumoral and stromal apolipoprotein-E (ApoE) decreases melanoma proliferation and metastasis and can increase the efficacy of vemurafenib, a BRAF inhibitor [103,104].…”
Section: Targeted Therapymentioning
confidence: 99%